KEPADATAN PERMUKIMAN DAN KETERSEDIAAN RUANG BERMAIN ANAK - Manurung, Parmonangan (Talenta Publisher, 2017)
The growth rate of people very rapidly with urbanization and density urban environments, had affected the availability of children's playground in informal settlements, especially in big cities. These conditions have adverse effects for the development of children who live in urban environments. Children as mandated by law, have the right to get a chance to play, on the other hand, play a part of the development of the child as well as a medium of learning. Base on this background, this paper aims to examine the influences of density informal settlements in urban environment for the availability of children's playground, especially friendly playground. This paper used qualitative research methods to conduct a literature study and observation to some locations where children play. The results showed that the density of settlement and urban growth over time reduces children's playground, and this will have an impact on the growth and development of children. From the discussion, it can be concluded that, an open space or a children-friendly playground in an informal settlement is needed in order to support the growth and development of children, because play is a very important activity in the process of their physical growth and social development.